NUTMEG EXTRACT POTENTIALLY ALTERS THE CHARACTERISTICS PROFILE OF ADIPOSE TISSUE 3T3-L1 CELL LINES - Aziiz Mardanarian Rosdianto; Ronny Lesmana; Iwan Setiawan; Yuni Susanti Pratiwi; Nurul Fadhilah; Ivan Christian Channel; Vita Mutia Tarawan (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2022)
Metabolic syndrome (MS) is currently emerging globally and increases the risk of dangerous chronic diseases. Obesity involving inflammatory mediators secreted by adipocytes appears to be the major cause. While white adipose tissue (WAT) functions as energy storage, brown adipose tissue (BAT) involves in thermogenesis and is known to have the ability to dissipate energy. Currently, researchers are developing BAT through the browning mechanism of adipose tissue to prevent and cure MS. The extract derived from nutmeg, a tropical seed of Myristica fragrans, has a peroxisome proliferator-activated receptor γ (PPARγ) agonistic effect which is known to stimulate brown adipocytes development. PPARγ activation stimulates the expression of uncoupling protein 1 (UCP1), uncoupling protein 2 (UCP2), and uncoupling protein 3 (UCP3). In the present study, we explore nutmeg-induced stimulation of UCP1, UCP2, and UCP3 protein level characterization shift in 3T3- L1 cell lines which indicates the browning mechanism of adipose tissue exerted by nutmeg. Nutmeg was first extracted and 3T3-L1 cell lines taken from ATCC were used which were grown in Dulbecco’s Modified Eagle Medium (DMEM). Cells were treated with nutmeg extract (NuSE) with dose: 0.01; 0.1; 1; and 10 ppm. Western blot and ImageJ software were used for protein analysis and all experimental data were analyzed using SPSS. Results showed that NuSE stimulates the increase of UCP1 and UCP2 protein levels significantly at a 10-ppm dose. This suggests that polyphenol- containing malignant in NuSE has the probability to regulate PPARγ which potentially alters characteristics of white adipose tissue in 3T3-L1 cell lines.